Structure and substructure variations of icosahedral Ti₄₁.₅Zr₄₁.₅Ni₁₇ quasicrystals under irradiation imitating outer space factors - Bazdyreva, S.V.; Borisova, S.S.; Malykhin, S.V.; Pugachov, A.T.; Bovda, A.M.; Lavrinenko, S.D.; Abraimov, V.V.; Lototskaja, V.A. (Functional Materials, 2015)
The article presents the results of studying the changes of coherent length, micro-strain value, density of phason defects and residual macro-stresses in Ti₄₁.₅Zr₄₁.₅Ni₁₇ icosahedral quasi-crystalline ribbons after irradiation by VUV (hν = 10.2 eV, duration up to 40 h), electron and proton fluxes (hν = 100 KeV with doses D up to 13·10¹⁶ cm⁻²), X-ray bremsstrallung (hν = 1 MeV with doses D up to 10000 rad). It is shown that the scale of the substructure changes, defect density, their type and parameters depend on the perfection degree of the original structure and impact energy power.